A History of Rome from 133 B. C. to 70 A. D. (1904) : From the Tribunate of Tiberius Gracchus to the End of the Jugerthine War - Greenidge, A. H. J. (Routledge Revivals Ser, 2018)
Cover -- Half Title -- Title -- Copyright -- Title Original -- Copyright Original -- Dedication -- Preface -- CONTENTS -- CHAPTER I -- CHAPTER II -- CHAPTER III -- CHAPTER IV -- CHAPTER V -- CHAPTER VI -- CHAPTER VII -- CHAPTER VIII -- MAPS -- The Wäd Mellag and the surrounding territory -- Numidia and the Roman Province of Africa -- Titles of modern works referred to in the notes -- Index.